Adult neuroplasticity employs developmental mechanisms - Mowery, Todd M.; Garraghty, Preston E. (Frontiers in Systems Neuroscience, 2023)
Although neural plasticity is now widely studied, there was a time when the idea of adult plasticity was antithetical to the mainstream. The essential stumbling block arose from the seminal experiments of Hubel and Wiesel who presented convincing evidence that there existed a critical period for plasticity during development after which the brain lost its ability to change in accordance to shifts in sensory input. Despite the zeitgeist that mature brain is relatively immutable to change, there were a number of examples of adult neural plasticity emerging in the scientific literature. Interestingly, some of the earliest of these studies involved visual plasticity in the adult cat. Even earlier, there were reports of what appeared to be functional reorganization in adult rat somatosensory thalamus after dorsal column lesions, a finding that was confirmed and extended with additional experimentation. To demonstrate that these findings reflected more than a response to central injury, and to gain greater control of the extent of the sensory loss, peripheral nerve injuries were used that eliminated ascending sensory information while leaving central pathways intact. Merzenich, Kaas, and colleagues used peripheral nerve transections to reveal unambiguous reorganization in primate somatosensory cortex. Moreover, these same researchers showed that this plasticity proceeded in no less than two stages, one immediate, and one more protracted. These findings were confirmed and extended to more expansive cortical deprivations, and further extended to the thalamus and brainstem. There then began a series of experiments to reveal the physiological, morphological and neurochemical mechanisms that permitted this plasticity. Ultimately, Mowery and colleagues conducted a series of experiments that carefully tracked the levels of expression of several subunits of glutamate (AMPA and NMDA) and GABA (GABAA and GABAB) receptor complexes in primate somatosensory cortex at several time points after peripheral nerve injury. These receptor subunit mapping experiments revealed that membrane expression levels came to reflect those seen in early phases of critical period development. This suggested that under conditions of prolonged sensory deprivation the adult cells were returning to critical period like plastic states, i.e., developmental recapitulation. Here we outline the heuristics that drive this phenomenon.